2019
DOI: 10.1021/acs.jafc.8b06483
|View full text |Cite
|
Sign up to set email alerts
|

An Improved, Rapid, and Sensitive Ultra-High-Performance Liquid Chromatography-High-Resolution Orbitrap Mass Spectrometry Analysis for the Determination of Highly Polar Pesticides and Contaminants in Processed Fruits and Vegetables

Abstract: A rapid, specific, and sensitive method based on quick polar pesticide extraction and ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry with an Orbitrap analyzer was evaluated. Usually, pesticides were analyzed individually using derivatization or ion-pairing techniques and detection by ion chromatography. We identified and simultaneously quantified 6 highly polar compounds (glyphosate, aminomethyl phosphonic acid (AMPA), phosphonic acid, fosetyl-Al, chlorate, and perchl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…• Quantification of pesticides residues in food [24][25][26] • Amino acid profiling [9,27] • Multi-drug residue quantitation in food matrix [28] • Metabolomics study in food safety [9] • Analysis of food contaminants in food matrices • Analysis of natural medicine and herbal medicine [9] • Determination of acrylamide in food matrix [29] • Analysis of mycotoxin in food [30,31] • Determination of bromate in drinking water [32] • Pesticide in fruit and vegetables [33] • Determination of food-borne carcinogens heterocyclic amines [34] • Capsaicinoids analysis in capsicum species [35] • Analysis of vitamin in food…”
Section: Application Of Ultra Performance Liquid Chromatography In Fomentioning
confidence: 99%
See 1 more Smart Citation
“…• Quantification of pesticides residues in food [24][25][26] • Amino acid profiling [9,27] • Multi-drug residue quantitation in food matrix [28] • Metabolomics study in food safety [9] • Analysis of food contaminants in food matrices • Analysis of natural medicine and herbal medicine [9] • Determination of acrylamide in food matrix [29] • Analysis of mycotoxin in food [30,31] • Determination of bromate in drinking water [32] • Pesticide in fruit and vegetables [33] • Determination of food-borne carcinogens heterocyclic amines [34] • Capsaicinoids analysis in capsicum species [35] • Analysis of vitamin in food…”
Section: Application Of Ultra Performance Liquid Chromatography In Fomentioning
confidence: 99%
“…However, it has been reported that, these chemical has very harmful effect on human health [52]. Savini et al [33] reported a quick and sensitive UPLC method coupled with Orbitrap for determining highly polar pesticides and contaminants in processed fruits and vegetables.…”
Section: Pesticides In Fruit and Vegetablesmentioning
confidence: 99%
“…As it can be observed, liquid chromatography is particularly appropriate for the analysis of polar, non-volatile, and/or thermally labile pesticides. Because of its high selectivity and sensitivity, HPLC and UHPLC in combination with MS/MS have mostly been used in this field especially to determine the insecticides and herbicides belonging to organophosphorus compounds, imidazolinone and pyridine carboxylic acid derivatives, and in study of samples containing multiclass pesticides [16][17][18][19][20][21][22][23][24]27,[30][31][32][33][34]. However, in a few cases, i.e., triazine and phenylurea herbicides, the HPLC coupled with spectrophotometric detection HPLC-UV or DAD has also been applied [25,26,28].…”
Section: Column Liqiud Chromatography In Analysis Of Selected Bioactive Compounds In Food Samplesmentioning
confidence: 99%
“…Melton et al still used the ion chromatography but coupled with the tandem mass spectrometry (IC-MS/MS) for determining highly polar pesticides (including GLY, AMPA, and GLU) in 288 samples of melon, peas without pods, and pineapple [81]. Finally, a paper by Savini et al worth to be mentioned: the authors used the UHPLC coupled with a orbitrap detector for analyzing GLPY, AMPA, GLUF, and other polar pesticides in 98 samples (83 processed fruits and vegetables and 15 infant foods) [82]. Using the developed method, the authors obtained LOQ of 0.003 mg kg −1 for all three compounds, recoveries 75-113% in all matrices, RSDs below 18.5%, and a R 2 between 0.9954 and 0.9998 in the linear range of 0.001-0.1 mg L −1 .…”
Section: Vegetablesmentioning
confidence: 99%